Efficacy of combined surgery and pembrolizumab for the treatment of pulmonary large cell carcinoma: a case report - Gu, Linguo; Chen, Hongzuo; Xia, Zhenkun; Qing, Bei; Yuan, Yunchang (Frontiers in Immunology, 2024)
Pulmonary large cell carcinoma (LCC) is a rare and aggressive subtype of non-small cell lung cancer (NSCLC) with poor prognosis. Surgical resection remains the cornerstone of treatment for resectable LCC; however, its efficacy is limited in advanced stages, necessitating adjuvant therapies to reduce postoperative recurrence risk. Recent advances in immunotherapy have shown promising survival benefits. Here, we present a case of LCC successfully treated with a combination of surgery and pembrolizumab. A 56-year-old male smoker, diagnosed with LCC and staged as T2N1M0 postoperatively, developed recurrent disease one month after surgery, as evidenced by enlarged left hilar and mediastinal lymph nodes on chest CT. The patient received adjuvant chemotherapy and immunotherapy, guided by high PD-L1 expression. However, after three cycles, chemotherapy was discontinued due to severe side effects, and pembrolizumab monotherapy was initiated. After 21 cycles, there was substantial regression of the mediastinal and hilar lymph nodes. The patient remained progression-free after 24 cycles of treatment. This case underscores the potential of combining surgical resection with immunotherapy as an effective strategy not only for resectable LCC but also for other rare NSCLC subtypes with high PD-L1 expression.